2015
DOI: 10.1007/s12194-015-0341-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of subject thickness on the exposure index in digital radiography

Abstract: The exposure index (EI) was proposed as a new X-ray dose index by the International Electrotechnical Commission (IEC) and has since been implemented as an international standard. The EI is calculated by use of an approximation equation under IEC-specified calibration conditions. However, several factors encountered in clinical practice, including the patient's body thickness and the tube voltage, differ with regard to these calibration conditions. We, therefore, require a solid water phantom-based function tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…However, the clinical EI of both chest PA and LAT projection did not indicate a similar tendency with ESD, and the phantom distance compared with those of ESD. Takaki et al reported that the EI, as per the IEC standards framework, depends on the PMMA phantom thickness, and thus EI should be introduced cautiously for children and thin patients [ 26 ]. Sánchez et al proposed that the thickness-based techniques for portable pediatric abdomen radiography should be used to reduce the variability in EI because default pediatric protocols do not adequately characterize the patient size, which is the principal determinant of proper imaging technique [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical EI of both chest PA and LAT projection did not indicate a similar tendency with ESD, and the phantom distance compared with those of ESD. Takaki et al reported that the EI, as per the IEC standards framework, depends on the PMMA phantom thickness, and thus EI should be introduced cautiously for children and thin patients [ 26 ]. Sánchez et al proposed that the thickness-based techniques for portable pediatric abdomen radiography should be used to reduce the variability in EI because default pediatric protocols do not adequately characterize the patient size, which is the principal determinant of proper imaging technique [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of factors contribute to this variation in EI value, including variable collimation 35 and segmentation by the EI algorithm. There is also the known dependence of EI with patient thickness: 36 patients with different thickness and anatomy will produce a change in the beam quality, which then influences the EI value. 16 In Fig.…”
Section: Comparison Of the Lungman Phantom To Patients Using Ei Kapmentioning
confidence: 99%
“…To remove the noise level on image in DR system, the radiologic technologists (RTs) is forced to raise the image parameters. However, the increase in the image parameters produce a readable image (Takaki et al, 2016) (Muntaser S Ahmad et al, 2019). The extent of the increase in parameters increase radiation dose to patients.…”
Section: Introductionmentioning
confidence: 99%
“…The EI is used as a quality control tool to check the image quality, because the EI is proportional to the square signal to noise ratio (SNR) (Takaki et al, 2016) (Martin et al, 2017). The EI values for radiological examinations vary according to the manufacturer, each of manufacturer has specific values for the EI.…”
Section: Introductionmentioning
confidence: 99%